Facilities and Infrastructure Management as a Strategic Pillar of Islamic Educational Governance: A Multiple-Case Study of Graduation Productivity at Public Senior High Schools in Jambi Province - Sahudi Ramli; Ahmad Syukri; Samsu (CV. Kalimasada Group, 2026)
Effective management of educational facilities and infrastructure constitutes a strategic organizational capability that directly influences institutional productivity and graduate quality. Grounded in the principles of Islamic educational management—particularly the concepts of amanah (trusteeship), masʼuliyyah (accountability), and ihsan (excellence)—this study investigates how facilities and infrastructure management contributes to improving graduation productivity at public senior high schools in Jambi Province, Indonesia. A qualitative multiple-case study design was employed, involving three purposively selected schools representing urban, semi-urban, and rural contexts. Data were generated through participatory observation, semi-structured interviews with 24 participants, and document analysis, and were analyzed using Braun and Clarke's (2022) thematic analysis framework assisted by NVivo 15. Six interrelated managerial dimensions were identified: strategic planning, optimal facility utilization, preventive maintenance, digital infrastructure integration, collaborative leadership, and constraint management. Schools that consistently apply Islamic management principles across all six dimensions demonstrate higher graduation productivity and graduate quality. The study contributes to the discourse on Islamic educational management by reconceptualizing facilities management as a strategic, values-driven organizational capability rather than a mere administrative function.